Exploring careers in the military services - Macdonald, Robert W. (Military opportunity series, 1987)
An informative guide to military careers, including chapters on each of the services, descriptions of military life and discussion of its pros and cons, a list of military jobs and equivalent civilian jobs, plus lists of pay grades, college ROTC programs, military occupations and sources of further information